Assessment of arterial stiffness using oscillometric arteriography - Jatoi, Noor Ahmed (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Pharmacology & Therapeutics, 2009)
The present series of studies examined whether an oscillometric method (Arteriograph), which measures arterial stiffness indices, pulse wave velocity (PWV m/sec), and wave reflection as augmentation index [Alx %], is on accurate and reliable method when compared with two standard techniques using SphygmoCor and Complior in normal healthy subjects and untreated hypertensive patients. In addition of arterial stiffness, the determinants e.g. smoking status; stress (physical and mental) and environmental changes and the effect of therapeutic intervention on arterial stiffness were assessed with this technique.
Keywords: Pharmacology, Ph.D.; Ph.D. Trinity College Dublin